Mortality associated with metabolic syndrome in people with COPD managed in primary care. Issue 4 (24th October 2022) - Karsanji, Urvee; Evans, Rachael A.; Quint, Jennifer K.; Khunti, Kamlesh; Lawson, Claire A.; Petherick, Emily; Greening, Neil J.; Singh, Sally J.; Richardson, Matthew; Steiner, Michael C.
Objective: The prevalence of metabolic syndrome (MetS) has been reported to be higher in selected populations of people with COPD. The impact of MetS on mortality in COPD is unknown. We used routinely collected healthcare data to estimate the prevalence of MetS in people with COPD managed in primary care and determine its impact on 5-year mortality. Methods: Records from 103 955 patients with COPD from the Clinical Practice Research Datalink (CPRD-GOLD) between 2009 to 2017 were scrutinised. MetS was defined as the presence of three or more of: obesity, hypertension, lowered high-density lipoprotein cholesterol, elevated triglycerides or type 2 diabetes mellitus (T2DM). Univariate and multivariable Cox regression models were constructed to determine the prognostic impact of MetS on 5-year mortality. Similar univariate models were constructed for individual components of the definition of MetS. Results: The prevalence of MetS in the COPD cohort was 10.1%. Univariate analyses showed the presence of MetS increased mortality (hazard ratio (HR) 1.19, 95% CI: 1.12–1.27, p<0.001), but this risk was substantially attenuated in the multivariable analysis (HR 1.06, 95% CI: 0.99–1.13, p = 0.085). The presence of hypertension (HR 1.70, 95% CI: 1.63–1.77, p<0.001) and T2DM (HR 1.41, 95% CI: 1.34–1.48, p<0.001) increased and obesity (HR 0.74, 95% CI: 0.71–0.78, p<0.001) reduced mortality risk. Conclusion: MetS in patients with COPD is associated with higher 5-year mortality, but this impact was minimal when adjusted for indices of COPD disease severity and other comorbidities. Individual components of the MetS definition exerted differential impacts on mortality suggesting limitation to the use of MetS as a multicomponent condition in predicting outcome in COPD. The presence of MetS in COPD is not significantly associated with increased mortality over 5 years. The individual components of MetS exert differential effects on mortality, limiting the utility of the syndrome in predicting outcome. https://bit.ly/3PooGQd